MANAGING HEART RELATED DISEASE RISKS IN BPJS KESEHATAN USING COLLECTIVE RISK MODELS - Gede Ary Prabha Yogesswara; Danang Teguh Qoyyimi; Abdurakhman Abdurakhman (Department of Statistics, Faculty of Science and Mathematics, Universitas Diponegoro, 2022)
BPJS Kesehatan is a legal entity established to administer the health service program using the insurance system. Heart related diseases is a disease with the largest coverage cost in Indonesia. It can be calculated by using the collective risk model as an approximation of the aggregate loss model. This model is a compound distribution from claim frequency and claim severity, where claim frequency be the primary distributions. The Poisson distribution can be used to the distribution of the heart disease claim frequency. Whereas, the distribution of the heart disease claim severity has a lognormal distribution. The model obtained can explain the aggregate loss of heart disease claims properly.